2008
DOI: 10.1016/j.fcr.2007.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Within-field variability of wheat yield and economic implications for spatially variable nutrient management

Abstract: Economic justification for varying fertiliser inputs to match crop yield potential of different areas or zones in fields is limited by lack of understanding of the relationship between the extent of within-field yield variation and economic gains from zone vs. uniform management. We conducted a survey of yield monitor data from 199 fields on the northern sandplain of the wheatbelt in Western Australia in order to document the extent of sub-field yield variation and test if variation is related to attributes su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 13 publications
3
25
0
2
Order By: Relevance
“…'', and ''What is holding you back in adopting PA?''. For the purposes of defining ''manageable variability'' we followed the rule-of-thumb developed by Robertson et al (2008) where a difference between zones in wheat yield potential of at least 1 t/ha would constitute enough to justify financially the use of variable rate application of fertiliser.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…'', and ''What is holding you back in adopting PA?''. For the purposes of defining ''manageable variability'' we followed the rule-of-thumb developed by Robertson et al (2008) where a difference between zones in wheat yield potential of at least 1 t/ha would constitute enough to justify financially the use of variable rate application of fertiliser.…”
Section: Methodsmentioning
confidence: 99%
“…Published Australian studies of economic analysis of VR fertiliser in broadacre grain production include experimental comparisons, case studies of farmers who have adopted the technology, and economic modelling based on both representative and actual farms and fields (Brennan et al 2007;Robertson et al 2007;Robertson et al 2008;Robertson et al 2009). The benefits range from close to zero to around AUD50/ha.…”
Section: Relative Advantagementioning
confidence: 99%
“…It does seem likely, however, that N 2 O emission and NO -3 leaching can be reduced by applying N in a spatially variable way, since several studies have found no loss of yield with a reduction in total N applied (e.g. [33][34][35]). Savings in these terms have rarely been identified in the literature but could be substantial in global or national terms if most emissions derive from the under-use of applied N by crops (perhaps 1-2 kg N 2 O-N ha …”
Section: Improve Effectiveness Of Extension (E)mentioning
confidence: 99%
“…Firstly, they could assist growers who have not yet adopted, or those who have recently adopted, precision agriculture technology to more readily access its benefits by extending the length of the dataset that is available for crop management decision making [34,35]. This would allow land managers to assess the spatially explicit nature of productivity, fertiliser requirements and profitability of their fields from a longer time series [36] and therefore leap-frog the time consuming process of archiving annual yield maps generally used in this assessment process.…”
Section: Introductionmentioning
confidence: 99%